Determining Firm Value: Profitability, Leverage, and Ownership in LQ45 (2020–2024) - Prastyawan, Tangguh Bakit; Suhendah, Rousilita (Penerbit Goodwood, 2025)
Purpose: This research aims to determine the the influence of profitability, leverage, managerial ownership, institutional ownership, and foreign ownership on the firm value of companies listed in the LQ45 index during the period 2020–2024. Methodology/approach: This research is a quantitative research with a descriptive approach. The sample was selected using the purposive sampling method and valid data were 19 companies. The data processing technique used multiple regression analysis assisted by EViews software version 12. Results/findings: The results obtained from this study are that profitability has no effect on company value, leverage has a significant negative effect on company value, managerial ownership and institutional ownership have a significant positive effect on company value, foreign ownership has no effect on company value. Conclusions: Profitability has no effect on firm value (H1 rejected), leverage has a negative effect on firm value (H2 accepted), managerial ownership has a positive effect on firm value (H3 accepted), institutional ownership has a positive effect on firm value (H4 accepted) and foreign ownership has no effect on firm value (H5 rejected). Limitations: This study is limited by the use of secondary data that is not always complete, the 2020–2024 time period which was affected by the COVID-19 pandemic, limited independent variables, and does not include qualitative factors such as management quality and corporate governance. Contribution: This research can be used as a reference for further research, especially research that discusses the determination of firm value.